Reviews - Philip Barker; John Knight; Ray McAleese; Philip Barker (Association for Learning Technology, 2003)
The Internet and its many aspects, including the use of the increasingly media-rich World Wide Web and online communication tools is becoming increasingly central to teaching and learning across the whole educational spectrum. Nevertheless, despite directives such as the National Grid for Learning, which has led to near universal, if still uneven,